Effect of SDBS on the drag reduction characteristics of polyacrylamide in a rotating disk apparatus - Bari, Hayder A. Abdul; Yousif, Zainab; Yaacob, Zulkefli Bin; Oluwasogaakindoyo, Edward (International Journal of Basic and Applied Sciences, 2015)
This paper focuses on the determination of the interaction between polymer (Polyacrylamide (PAM)) and surfactant (Sodium dod benzene sulfonate (SDBS)) as a drag reducer using Rotating Disk apparatus (RDA) at various concentrations (500, 700, 1000, 1500 and 2000) ppm individually and in the combined form under turbulent conditions at different rotation speed up to 3000 rpm, as well as studying their mechanisms as a drag reducer. The results show that the maximum percent drag reduction increases to (40, 41, 43, 45 and 48)% by using the combined additives of surfactant and polymer at the above concentrations respectively, with slower degradation and display drag reduction for a larger range of Reynolds numbers. The nano and micro particles formed from the combined PAA and SDBSA was studied using cryo-transmission electron microscopy (cryo-TEM) techniques. The images show the surrounding of polymer chain to the surfactant micelle to form an aggregate structure. A hexagonal crystalline form was suggested to describe the shape of the aggregate structure.